Application of a convex appliance to restore peristomal skin integrity: a case study - Fengzhi & Yan and & Mengxiao Jiang (WCET Journal - Portuguese Edition, 2020)
This case study describes the nursing management of one case of irritant contact dermatitis from faecal fluid around the peristomal skin of a patient with an ileostomy who presented to the outpatient department 1 month postoperatively. This postoperative complication occurred as a result of the stoma being located within wrinkles in the abdomen, causing the appliance to leak and skin ulceration to develop, which prevented firm adherence of the appliance base plate to the peristomal skin. Furthermore, the patient was very anxious as a result of these complications. In this patient’s case, the initial goals were to assess and address the peristomal skin complications, provide an appliance with convexity that could be fixed with a belt to stabilise the appliance as early as possible, and finally commence strengthening psychological counselling and dietary guidance for the patient and her family. These nursing interventions were found to reduce the incidence of faecal dermatitis complications around the stoma, improve the patient’s quality of life and thus worth applying.